Mycobacterium massiliense BRA100 strain recovered from postsurgical infections: resistance to high concentrations of glutaraldehyde and alternative solutions for high level disinfection - Lorena,Nádia Suely de Oliveira (2010)
PURPOSE: To evaluate the minimum inhibitory concentration (MIC) of GTA against these microorganisms and alternative disinfectants for high-level disinfection (HLD). METHODS: Reference mycobacteria and clinical M. massiliense strains were included in this study. Active cultures were submitted to susceptibility qualitative tests with GTA dilutions (ranging from 1.5% to 8%), and commercial orthophthaldehyde (OPA) and peracetic acid (PA) - based solutions, during the period of exposure as recommended by National Agency of Sanitary Surveillance for HLD. RESULTS: All reference and M. massiliense non-BRA100 strains, recovered from sputum, were susceptible to any GTA concentration, OPA and PA solutions. M. massiliense BRA100 strains presented MIC of 8% GTA and were susceptible to OPA and PA. CONCLUSION: M. massiliense BRA100 strain is resistant to high GTA concentrations (up to 7%), which proves that this product is non-effective against specific rapidly growing mycobacteria and should be substituted by OPA or PA - based solutions for HLD.